الحرية وجذور الفكر الجبري في ثقافتنا العربية. - كرومي, عبد الحكيم (roa, 2021)
تحاول هذه الورقة الحفر عن جذور الأسباب التي حالت دون تبلور نظرية مركبة وشاملة لمسألة الحرية في المجال التداولي العربي، حيث تكرست رؤية مختزلة للحرية كان إطارها المرجعي الوحيد الذي تتحرك فيه هو حقل الرق والعبودية ، وللبرهنة على ذلك تنطلق من فرضية أن هناك عوامل سياسية أسهمت من جهة على اختزال هذه القضية المعقدة وتبسيطها في دلالات معنية على حساب دلالات أخرى كان من الممكن أن تغني تلك القضية وتجعلها خصبة وثرية، ومن جهة أخرى فقد انتهت تلك العوامل إلى غرس البذور الأولى للفكر الجبري التسلطي في نسيج الثقافة العربية، إلى أصبح هذ الفكر في المحصلة هو أحد المقومات والمرتكزات التي تستند عليها الدولة في سياقنا العربي. الكلمات المفتاحية: الحرية، الجبرية والجبرية الجديدة، الاختيار، الفعل الإنساني.   Abstract This paper attempts to explore the roots of the causes that prevented the formulation of a complex and comprehensive theory about freedom in the Arab deliberative field. The paper argues that there has been a perpetuated reductionist view of freedom considered to be the opposite of slavery as the sole understanding of this notion. To prove this, this paper departs from the hypothesis that there has been political reasons that contributed, on the one hand, in perpetuating this reductionist view to freedom, and on the other hand in implanting the first roots of the compulsivity thought within the Arabic cultural fabric to the extent that made this thought become one of the foundational pillars that sustain contemporary states in the Arab context. Key words : Freedom, compulsivity and the new compulsivity thought, the choice, the human deeds.